ANALISIS UPAYA GURU MATA PELAJARAN PENDIDIKAN PANCASILA DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SMP NEGERI 1 TULUNG SELAPAN - Septriadi, M. Ghaniy; Sri Artati Waluyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the efforts of Civic Education teachers in enhancing students’ learning motivation at SMP Negeri 1 Tulung Selapan. This research employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. The findings reveal that teachers applied various strategies to foster students’ learning motivation. First, providing rewards and appreciation in the form of verbal praise, thumbs-up gestures, good grades, and simple gifts such as snacks and stationery. Second, creating a conducive learning atmosphere by maintaining classroom cleanliness, arranging seats neatly, and beginning lessons with ice-breaking activities. Third, applying varied teaching methods such as lectures, group discussions, question-and-answer sessions, quizzes, and educational games like crossword puzzles and word scrambles. Fourth, implementing objective assessments based on the Minimum Mastery Criteria (KKM) and offering remedial programs for students who had not met the standard. Fifth, delivering feedback in the form of praise, corrections, learning summaries, and constructive suggestions. Lastly, fostering positive relationships with students through open communication, providing opportunities for discussion, and resolving conflicts wisely.These findings are in line with experts’ opinions that learning motivation is influenced by both intrinsic and extrinsic factors. Teachers’ efforts in giving rewards, creating a comfortable learning environment, employing varied teaching methods, and building positive relationships with students have been proven to increase enthusiasm, interest, and participation in the learning process. Therefore, teachers play roles not only as knowledge transmitters but also as facilitators and motivators in education.